A quality assessment of reporting sources for microcephaly in Utah, 2003 to 2013. Issue 11 (November 2016) - Steele, Amy; Johnson, Jane; Nance, Amy; Satterfield, Robert; Alverson, C.J.; Mai, Cara
Abstract : Background: Obtaining accurate microcephaly prevalence is important given the recent association between microcephaly and Zika virus. Assessing the quality of data sources can guide surveillance programs as they focus their data collection efforts. The Utah Birth Defect Network (UBDN) has monitored microcephaly by data sources since 2003. The objective of this study was to examine the impact of reporting sources for microcephaly surveillance. Methods: All reported cases of microcephaly among Utah mothers from 2003 to 2013 were clinically reviewed and confirmed. The UBDN database was linked to state vital records and hospital discharge data for analysis. Reporting sources were analyzed for positive predictive value and sensitivity. Results: Of the 477 reported cases of microcephaly, 251 (52.6%) were confirmed as true cases. The UBDN identified 94 additional cases that were reported to the surveillance system as another birth defect, but were ultimately determined to be true microcephaly cases. The prevalence for microcephaly based on the UBDN medical record abstraction and clinical review was 8.2 per 10, 000 live births. Data sources varied in the number and accuracy of reporting, but a case was more likely to be a true case if identified from multiple sources than from a single source. Conclusion: While some reporting sources are more likely to identify possible and true microcephaly cases, maintaining a multiple source methodology allows for more complete case ascertainment. Surveillance programs should conduct periodic assessments of data sources to ensure their systems are capturing all possible birth defects cases. Birth Defects Research (Part A) 106:983–988, 2016. © 2016 Wiley Periodicals, Inc.